High frequency and amplitude effects in vibratory media finishing - Pandiyan, Vigneashwara (2019)
The vibratory media finishing process is known for its long process time and there is an industrial need to speed up this process. Increasing frequency and amplitude of vibration, beyond the current process window commonly used, is an option to reduce process time. Using a laboratory scale electro-magnetic shaker setup, the effects of increasing frequency and amplitude of vibration is investigated. By monitoring the surface roughness with processing time it is shown that, while for a given amplitude frequency has a strong effect, amplitude in general has a stronger effect in quickening the time to saturation. Using high-speed camera measurements in a transparent bowl it is also shown that the average media speed increases with increase in frequency and this can partially explain the resulting shorter process time.